Cephalosporin‐resistant Escherichia coli isolated from farm workers and pigs in northern Vietnam. Issue 4 (10th April 2018) - Dang, Son T. T.; Bortolaia, Valeria; Tran, Nhat T.; Le, Huan Q.; Dalsgaard, Anders
Abstract: Objective: Antimicrobial‐resistant bacteria may be transmitted between farm workers and livestock. This study aimed to determine and compare the prevalence and the genetic determinants of cefotaxime‐resistant and ESBL‐producing Escherichia coli in faecal isolates from workers and pigs at 100 farms in northern Vietnam. Methods: Farmers were interviewed about antimicrobial usage in livestock. Escherichia coli isolated on MacConkey agar containing 2 mg/l of cefotaxime (CTX) were tested for susceptibility to different cephalosporins by disc diffusion and screened for occurrence of ESBL‐encoding genes by PCR. Results: Antimicrobial usage was widespread and included classes regarded of critical or high importance in human medicine. Dosages were 0.5–2 times higher than recommended, and antimicrobials were often administered right until slaughter. Prevalence of CTX‐resistant E. coli was 86% in farm workers and 89% in pigs. In 76% of farms, CTX‐resistant E. coli were shared by pigs and farm workers. ESBL‐producing E. coli were detected from pigs and workers at 66 and 69 farms, respectively. The ESBL phenotype was mainly mediated by CTX‐M and to a lesser extent by TEM. Occurrence of bla CTX ‐M was similar in E. coli from pigs (66.7%) and humans (68.5%). Conclusion: The high occurrence of ESBL‐producing E. coli in pig farmers and pigs could present a risk for spillover of these bacteria from pig farms into the community. Genomic studies are needed to elucidate reservoirs and transmission routes of ESBL‐producing E. coli at livestock farms.